2008
DOI: 10.1210/jc.2007-2013
|View full text |Cite
|
Sign up to set email alerts
|

Late Recurrences of Cushing’s Disease after Initial Successful Transsphenoidal Surgery

Abstract: A quarter of the patients with Cushing's disease who achieve surgical remission after transsphenoidal surgery, recur with long-term follow-up. This finding emphasizes the need for continued biochemical and clinical follow-up to ensure remission after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
195
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(220 citation statements)
references
References 29 publications
13
195
1
9
Order By: Relevance
“…As previously reported, remission rates were higher in patients with microadenomas vs macroadenomas and recurrence outcomes were worse in patients with macroadenomas compared with microadenomas (6). Interestingly, duration of follow-up had no influence on recurrence rates in our analysis, while it has been previously reported that the risk for recurrence increased with long-term follow-up (51). This suggests that certain types of tumor may be more aggressive than others and may recur early during the follow-up period.…”
Section: Discussioncontrasting
confidence: 56%
“…As previously reported, remission rates were higher in patients with microadenomas vs macroadenomas and recurrence outcomes were worse in patients with macroadenomas compared with microadenomas (6). Interestingly, duration of follow-up had no influence on recurrence rates in our analysis, while it has been previously reported that the risk for recurrence increased with long-term follow-up (51). This suggests that certain types of tumor may be more aggressive than others and may recur early during the follow-up period.…”
Section: Discussioncontrasting
confidence: 56%
“…In patients with Cushing disease (CD), the most common form of endogenous CS, surgical success rates are variable, ranging from 65 to 90% when performed by an experienced surgeon (6,7). Among those patients with successful outcomes following transsphenoidal surgery, 11 to 66% will go on to develop recurrence of hypercortisolism with long-term follow-up (6,(8)(9)(10)(11)(12). Therefore, additional medical interventions are often required to achieve remission or improve the clinical manifestations of CS.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, plasma cortisol levels considered were < 1.8 μg/dL during the first days after surgery for cure definition -this is a very strict criterion. Notably, the criteria for cure vary significantly in the studies from the last 25 years, justifying the variable surgical cure rates observed (29,30). In addition, the experience of the neurosurgeon is another important factor.…”
Section: Discussionmentioning
confidence: 99%